(untitled) (Revista de Artes Marciales Asiáticas, 2019)
Many authors dealing with martial arts and combat sports indicate that this form of activity contributes to limiting aggressive behavior towards other people. Contemporary psychological and pedagogical knowledge explains that empathy is one of the factors that determines a friendly and aggression-free attitude of people towards others. This study we compared the level of empathy between children practicing judo for a minimum of two years and their peers who did not practiced any martial art. Results showed higher levels of empathy in the group of judo practitioners. Judo trainers also agreed that judo participation may improve children’s emotional development (emotional self-regulation and emotional self-awareness).